Two-Dimensional Liquid Chromatography Purified GC/C/IRMS Doping Control Method: Analysis of Endogenous and Exogenous Sources in Urine Samples from Asian Subjects Administered a Low Dose of AICAR - Wang, Yirang; Fan, Jingyi; Fang, Xian; Zhuo, Yue; Xu, Siyan; Liao, Lei; Deng, Xiaojun; Liu, Bing (Journal of Chromatography A, 2024)
•This study has developed a method for tracing the source of AICAR based on two-dimensional liquid chromatography and GC/C/IRMS.•The automated 2D-HPLC separation technique separates the analyte in one step, enhancing the efficiency of detection.•Analysis of samples after low-dose AICAR administration indicates that the length of the detection window is positively correlated with the dosage of the administered drug. AICAR (5-amino-4-imidazolecarboxyamide ribonucleoside), as a metabolic modulator, is classified in the S4 category by the World Anti-Doping Agency (WADA). Carbon Isotope Ratio Mass Spectrometry (CIR) is the mainstream method for distinguishing the endogenous and exogenous sources of AICAR in urine due to the significant individual difference in the concentration. The purpose of this study is to establish a gas chromatography combustion Isotope Ratio Mass Spectrometry (GC/C/IRMS) method for AICAR based on efficient two-dimensional liquid chromatography (2D-HPLC) separation. In this study, an automated 2D-HPLC separation technique was used to separate and purify AICAR and endogenous reference substances in urine samples. Then, AICAR was derivatized with 3-TMS as the main derivative product, while the endogenous reference compounds remained in their original form. Subsequently, the developed GC/C/IRMS method was utilized for the detection of the target and reference substances. Followed, we evaluated the applicability of this method using urine samples from two Asian males administered a low dose of AICAR (3 grams). The advantages of this study include: 1) reduced sample pretreatment time: the established 2D-HPLC separation method can separate the target and endogenous reference substances in one step; 2) low interference: the isotope chromatograms have low background interference, and the separation of endogenous reference substances is purer; 3) more accurate result calculations: this method only requires derivatization and result correction for AICAR, with the endogenous reference substances measured in their original form, reducing biases from corrections of multiple substances. The detection method performed well, with a concentriton limit of 2500 ng/mL, meeting the needs of routine detection concentrations. The CIR results from volunteer samples indicated that samples collected within 16 hours post-administration exceeded the threshold set in the literature. This study successfully established a 2D-HPLC-GC/IRMS method that integrates CIR as the most stable indicator for distinguishing the internal and external sources of AICAR. After administering a low dose of AICAR to the Asian population, exogenous drug characteristics were manifested within 16 hours. This observation, when compared to the 40-hour detection window cited in the literature, suggests that the length of the detection window is positively correlated with the dosage of the test drug.